Comparative study of stereopsis with three different tests: TNO®, Stereo Acuity Test Fly® and StereoTAB® in students in higher school - Morais, Ruben (2016)
Purpose: Stereopsis is the perception of depth based on retinal disparity. Global stereopsis depends on the process of random dot stimuli and local stereopsis depends on contour perception. The aim of this study was to correlate 3 stereopsis tests: TNO®, StereoTA B®, and Fly Stereo Acuity Test® and to study the sensitivity and correlation between them, using TNO® as the gold standard. Other variables as near convergence point, vergences, symptoms and optical correction were correlated with the 3 tests. Materials and Methods: Forty-nine students from Escola Superior de Tecnologia da Saúde de Lisboa (ESTeSL), aged 18-26 years old were included. Results: The stereopsis mean (standard-deviation-SD) values in each test were: TNO® = 87.04” ±84.09”; FlyTest® = 38.18” ±34.59”; StereoTA B® = 124.89’’ ±137.38’’. About the coefficient of determination: TNO® and StereoTA B® with R2 = 0.6 e TNO® and FlyTest® with R2 =0.2. Pearson correlation coefficient shows a positive correlation between TNO® and StereoTA B® (r = 0.784 with α = 0.01). Phi coefficient shows a strong and positive association between TNO® and StereoTA B® (Φ = 0.848 with α = 0.01). In the ROC Curve, the StereoTA B® has an area under the curve bigger than the FlyTest® with a sensivity of 92.3% for 94.4% of specificity, so it means that the test is sensitive with a good discriminative power. Conclusion: We conclude that the use of Stereopsis tests to study global Stereopsis are an asset for clinical use. This type of test is more sensitive, revealing changes in Stereopsis when it is actually changed, unlike the test Stereopsis, which often indicates normal Stereopsis, camouflaging a Stereopsis change. We noted also that the StereoTA B ® is very sensitive and despite being a digital application, possessed good correlation with the TNO®.